The Potential of Sorghum Crops In Romania, In The Context of Climate Changes - Lazăr Carmen (Gurgu-Lazăr); Constanta Laura ZUGRAVU; Gheorghe Adrian ZUGRAVU (Communications of International Proceedings, 2023)
Sorghum is the fifth most cultivated cereal in the whole world, after wheat, rice, corn and barley. But this tasty and gluten-free cereal is quite little known and consumed in Romania. In Romania there are relatively few sorghum crops, although, along with amaranth, it was the basis of the Romanian diet in the 70s. It is a drought-resistant plant and much more nutritious than corn, which it resembles in many ways, sorghum can thus become a substitute for corn.
Keywords: sorg hum; climate change; drought resistant